2005
DOI: 10.1063/1.1895466
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of solution-processed methanofullerene-based organic field-effect transistors

Abstract: The fabrication and characterization of high-mobility, n-channel organic field-effect transistors ͑OFET͒ based on methanofullerene ͓6,6͔-phenyl C 61 -butyric acid methyl ester using various organic insulators as gate dielectrics is presented. Gate dielectrics not only influence the morphology of the active semiconductor, but also the distribution of the localized states at the semiconductor-dielectric interface. Spin-coated organic dielectrics with very smooth surfaces provide a well-defined interface for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(79 citation statements)
references
References 37 publications
2
75
1
1
Order By: Relevance
“…Electron mobility in C 60 film is about 1 cm 2 V −1 s −1 [20,23,24] so that C 60 is one of the most useful electron-transport materials. However, to achieve low-cost production and large-area devices, it is necessary for C 60 materials to have a solution-processable form, such as [6,6]-phenyl C 61 -butyric acid methyl ester (PCBM) [25]. Therefore, in organic electronics, the electronic properties of C 60 derivatives rather than those of the original C 60 are of much interest and importance.…”
Section: Motivationmentioning
confidence: 99%
“…Electron mobility in C 60 film is about 1 cm 2 V −1 s −1 [20,23,24] so that C 60 is one of the most useful electron-transport materials. However, to achieve low-cost production and large-area devices, it is necessary for C 60 materials to have a solution-processable form, such as [6,6]-phenyl C 61 -butyric acid methyl ester (PCBM) [25]. Therefore, in organic electronics, the electronic properties of C 60 derivatives rather than those of the original C 60 are of much interest and importance.…”
Section: Motivationmentioning
confidence: 99%
“…37 The electron mobility of fullerenes are of the order of 10 À3 cm 2 V À1 s À1 as measured in the space-chargelimited regime 38 or about 10 À1 cm 2 V À1 s À1 as measured in field-effect transistors, which is relatively higher than most polymer materials. 39 Therefore, for a balanced charge transport, it is necessary to enhance the hole mobility of the donor materials. It has been suggested that a molecular assembly consisting of an interdigitated network of donor and acceptor phases, comprising of well-ordered donor and acceptor within those phases, is the key to facilitate this process.…”
Section: Physical Processes In the Organic Solar Cellsmentioning
confidence: 99%
“…Further, while designing materials for organic solar cells, careful attention must be paid to ensure that the materials (a) can be synthesized in high purity at a low cost and be scalable; (b) have flexibility to make structural changes to tune their ionization potentials and electron affinities to optimize both band gap and V OC , coherently and/or independently; (c) possess good solubility in commonly used organic solvents; (d) are processable into thin-films that are thermally, chemically, and photochemically stable over a long period of time; (e) exhibits a high absorptivity and a panchromatic absorption; (f) are miscible with the acceptor and result in a fine phase segregation comprising of a bicontinuous donor and acceptor phases in thin films, 40,41 (g) exhibit optimum pÀp stacking and crystallinity to ensure high charge-carrier mobility, (h) have a low series resistance, to match the high electron mobility of fullerene materials. 38,39 These desired properties must be REVIEW synergistically integrated into one polymer system so that the PCE can be seamlessly optimized.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…circumstance of PVA dielectric, the charge transport in PVA bulk and the charge trapping/detrapping process in PVA bulk and/or at the interface of organic semiconductor/PVA are considered to be the origin of hysteresis. [16][17][18] Also, the electrical characteristic of device A varies significantly as the multi-test of device, which further verifies charge traps in PVA bulk or at the interface of PVA/pentacene. 23 Device B based on single PMMA (620 nm) exhibits almost no hysteresis in the transfer curve.…”
mentioning
confidence: 99%
“…T. B. Singh et al suggested that the charge trapping and detrapping process in the PVA is responsible for the hysteresis. 16 Lowering the temperature, the process of charge trapping and detrapping is proposed to be frozen out. M. Egginger et al concluded that the change in the volume charge distribution within PVA gate dielectric as well as the variation in the charge distribution at organic semiconductor/dielectric interface affect the hysteresis by the field induced polarization of dielectric.…”
mentioning
confidence: 99%